2000
DOI: 10.1063/1.372820
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hardening studies in sintered Sm(Co,Cux,Fe,Zr)z 2:17 high temperature magnets

Abstract: Lorentz microscopy combined with conventional transmission electron microscopy were used to image the magnetic domains and microstructures of sintered Sm͑Co bal Cu x Fe 0.06 Zr 0.03 ) z ͑0.088рx р0.128; 5.8рzр7.2͒ permanent magnets which were specifically designed for high temperature applications. The microstructural data were correlated with the magnetic measurements to understand the origin of coercivity. All sintered magnets showed typical cellular and lamellar microstructures. The cell size and coercivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…For most magnets, the coercivity is related to domain wall nucleation and propagation. While the domain nucleation mechanism is predominant in most rare-earth permanent bulk magnets like Nd-Fe-B magnets, it is generally agreed that coercivity of the Sm Co -based magnets is controlled by domain wall pinning [3]- [6]. Studies have shown that the SmCo -type cell boundaries act as domain wall pinning sites in Sm Co -based permanent magnets.…”
Section: Introductionmentioning
confidence: 98%
“…For most magnets, the coercivity is related to domain wall nucleation and propagation. While the domain nucleation mechanism is predominant in most rare-earth permanent bulk magnets like Nd-Fe-B magnets, it is generally agreed that coercivity of the Sm Co -based magnets is controlled by domain wall pinning [3]- [6]. Studies have shown that the SmCo -type cell boundaries act as domain wall pinning sites in Sm Co -based permanent magnets.…”
Section: Introductionmentioning
confidence: 98%
“…Although there have been numerous publications on Sm-Co 2:17-type magnets, only few magnetic domain characterizations on Sm-Co 2:17-type sintered magnets [13][14][15] have been reported. Zhang et al [13,14] studied the domain structure of the precipitation hardened 2:17-type Sm-Co magnets using Lorentz microscopy, revealing the pinning effect of domain walls.…”
Section: Introductionmentioning
confidence: 98%
“…Zhang et al [13,14] studied the domain structure of the precipitation hardened 2:17-type Sm-Co magnets using Lorentz microscopy, revealing the pinning effect of domain walls. It should be noted, however, that domain observation by TEM has only limited relevance concerning the domain structures of bulk materials and the change of those structures in a magnetization process because domain structures are very sensitive to the sample thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Sm(Co, Fe, Cu, Zr) z permanent magnets have excellent intrinsic magnetic properties such as very high Curie temperature (≥800 • C), high anisotropy fields (≥100 kOe) and relatively high saturation magnetizations (≥100 emu/g) [1,2]. Recently Sm(Co, Fe, Cu, Zr) z magnets have attracted considerable interest for high-temperature applications because of their large energy products and high-temperature performances [3,4].…”
Section: Introductionmentioning
confidence: 99%